Соціально-політичні маніпуляції особистістю - Короход, Ясміна Джанівна; Короход, Ясмина Джановна; Korohod, J. (My University, 2013)
The paper discusses a number of approaches, which are the foundation of the modern theory manipulation of mass consciousness. Highlights the main approaches to the definition of the term «manipulation» in the context of modern scientific discourse. The question of determining the place of manipulation in the political process of the. The author also examines some conditions of manipulation
Короход Я. Д. Соціально-політичні маніпуляції особистістю / Я. Д. Короход // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 268-275.
Keywords: теорія маніпулювання масовою свідомістю; поняття «маніпуляція»; місце маніпуляції в політичному процесі; умови маніпулювання; теория манипулирования массовым сознанием; понятие «манипуляция»; место манипуляции в политическом процессе; условия манипулирования; theory of manipulating the mass consciousness; the concept of "manipulation"; place the manipulation of the political process; manipulating conditions